2016
DOI: 10.1186/s12864-016-3378-7
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and diversification of the MSDIN family of cyclic peptide genes in the poisonous agarics Amanita phalloides and A. bisporigera

Abstract: BackgroundThe cyclic peptide toxins of Amanita mushrooms, such as α-amanitin and phalloidin, are encoded by the “MSDIN” gene family and ribosomally biosynthesized. Based on partial genome sequence and PCR analysis, some members of the MSDIN family were previously identified in Amanita bisporigera, and several other members are known from other species of Amanita. However, the complete complement in any one species, and hence the genetic capacity for these fungi to make cyclic peptides, remains unknown.ResultsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
76
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 48 publications
2
76
2
Order By: Relevance
“…It has been proven that lethal Amanita species are classified in the Amanita section Phalloideae and that these species contain the MSDIN gene family, allowing them to produce many small cyclopeptides, such as α-amanitin, on ribosomes [6,16]. In the present study, nine lethal Amanita species from China, including A. exitialis, A. fuliginea, A. mulliuscula, A. pallidorosea, A. rimosa, A. subfuliginea, A. subjunquillea, A. subpallidorosea and A. virosa, were proven to contain MSDIN genes, the same as other lethal Amanita species, such as A. bisporigera, described previously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been proven that lethal Amanita species are classified in the Amanita section Phalloideae and that these species contain the MSDIN gene family, allowing them to produce many small cyclopeptides, such as α-amanitin, on ribosomes [6,16]. In the present study, nine lethal Amanita species from China, including A. exitialis, A. fuliginea, A. mulliuscula, A. pallidorosea, A. rimosa, A. subfuliginea, A. subjunquillea, A. subpallidorosea and A. virosa, were proven to contain MSDIN genes, the same as other lethal Amanita species, such as A. bisporigera, described previously.…”
Section: Discussionmentioning
confidence: 99%
“…4 using degenerate primers [13]. Recently, Pulman et al (2016) showed by generating draft genome sequences of A. palloides and A. bisporigera that both possessed approximately 30 members of the MSDIN family, but only three of these genes were common to both [6]. Luo et al (2018) found 18 and 22 MSDIN genes in the A. subjunquillea and A. pallidorosea genomes through PacBio and Illumina sequencing, respectively [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations